TREND OF CHANGES ON THE ACADEMY OF CRIMINALISTIC AND POLICE STUDIES ENTRANCE EXAM - Janković, Radivoje; Koropanovski, Nenad (NBP. Nauka, bezbednosti, policija, 2017)
The aim of the research was to determine the trends of changes on The Academy of Criminalistic and Police Studies (ACPS) entrance exam. Furthermore, the paper is to find whether there are any differences between the sexes in the terms of the results of the entrance exam. 1576 examinees participated in the research (621 women and 955 men), all of which entered the ACPS as the students of basic and vocational studies. The paper analyses their scores in all components of the exam: High School Achievements (HSA), General Knowledge Test (GKT), Serbian Language and Literature Test (SLLT), the Level of Basic Motoric Abilities development (BMA) and the overall number of points achieved on the test. The results were firstly analysed by applying the basic descriptive statistics procedure which determined the equation of trend of changes and R-squared values. The existence of the general variability differences between groups was determined by using MANOVA, while for the determination of partial differences between pairs of variables the Bonferroni test was used. The positive changes trend for both sexes in HSA and the negative one in SLLT were demonstrated. In females, a positive trend in BMA and a negative GKT trend were observed. However, an opposite effect was detected in males. Nevertheless, despite the different trends in individual tests, the overall number of points achieved on the entrance exam demonstrated a positive trend of changes in both populations. MANOVA results showed that the women had statistically better results in HSA, SLLT and BMA variables, but worse results in GKT. The overall result on the entrance examination taken into account, the females had statistically better scores by 3.31%.